Targeting Cis-Regulatory Elements for Rice Grain Quality Improvement - Yu Ding; Jiannan Zhu; Dongsheng Zhao; Qiaoquan Liu; Qingqing Yang; Qingqing Yang; Tao Zhang (Frontiers in Plant Science, 2021)
Rice is the most important source of food worldwide, providing energy, and nutrition for more than half of the population worldwide. Rice grain quality is a complex trait that is affected by several factors, such as the genotype and environment, and is a major target for rice breeders. Cis-regulatory elements (CREs) are the regions of non-coding DNA, which play a critical role in gene expression regulation. Compared with gene knockout, CRE modifications can fine-tune the expression levels of target genes. Genome editing has provided opportunities to modify the genomes of organisms in a precise and predictable way. Recently, the promoter modifications of coding genes using genome editing technologies in plant improvement have become popular. In this study, we reviewed the results of recent studies on the identification, characterization, and application of CREs involved in rice grain quality. We proposed CREs as preferred potential targets to create allelic diversity and to improve quality traits via genome editing strategies in rice. We also discussed potential challenges and experimental considerations for the improvement in grain quality in crop plants.